Simulation-based evaluation of an in-vehicle smart situation awareness enhancement system - Gregoriades, Andreas; Sutcliffe, Alistair G. (My University, 2018)
Situation awareness (SA) constitutes a critical factor in road safety, strongly related to accidents. This paper describes the evaluation of a proposed SA enhancement system (SAES) that exploits augmented reality through a head-up display (HUD). Two SAES designs were evaluation (information rich vs. minimal information) using a custom-made simulator and the Situation Awareness Global Assessment Technique with performance and EEG measures. The paper describes the process of assessing the SA of drivers using the SAES, through a series of experiments with participants in a Cave Automatic Virtual Environment. The effectiveness of the SAES was tested in a within-group research design. The results showed that the information rich (radar-style display) was superior to the minimal (arrow hazard indicator) design and that both SAES improved drivers’ SA and performance compared to the control (no HUD) design. Practitioner Summary: Even though driver situation awareness is considered as one of the leading causes of road accidents, little has been done to enhance it. The current study demonstrates the positive effect of a proposed situation awareness enhancement system on driver situation awareness, through an experiment using virtual prototyping in a simulator.
Keywords: Driving simulation; Head-up display; Situation awareness; Virtual reality